Demand for livestock products in developing countries with a focus on quality and safety attributes: Evidence from Asia and Africa - Jabbar, M.A.; Baker, Derek; Fadiga, M.L. (International Livestock Research Institute, 2010)
Rising developing country demand for livestock products propelled by income and population growth, and by urbanization offers poverty reduction opportunities to actors in the supply chain. The increase in volumes demanded also features diversification and increased demand for quality attributes. Reliable food safety and information on animal husbandry and geographic origin have long been recognized as value-adding differentiation mechanisms in the developed world. Anecdotal accounts suggest that this is also the case in developing countries. However, little consistent rigorously researched evidence has been published on this subject. This report presents results based on case studies conducted in a number of developing countries in Asia and Africa—Bangladesh, Cambodia, Ethiopia, India, Kenya, Tunisia, and Vietnam. An overview of the theoretically consistent methods used and a synthesis of the results obtained in the various case studies are presented first followed by the case studies each describing a study of specific commodities in specific developing country locations. A consistent set of results emerges, wherein consumers exhibit willingness to pay for quality and safety in animal-origin foods, and within which this willingness to pay is strongest amongst the wealthy and the urban dwellers. However, the intricacy and variety of quality definition and measurement are demonstrated fully, as they occur between and within countries, commodity groups and other settings. The key message from the results is the evidence that quality and safety considerations in products of animal origin food provide commercial opportunities for developing country producers, market actors and industry participants.